Very high-cycle fatigue properties and microstructural damage mechanisms of selective laser melted AlSi10Mg alloy. (July 2019) - Awd, Mustafa; Siddique, Shafaqat; Johannsen, Jan; Emmelmann, Claus; Walther, Frank
Highlights: Influence of microstructural homogeneity on fatigue strength. Very high-cycle fatigue properties of selective laser melted AlSi10Mg. Fatigue cracking analysis in X-ray computed tomography. Abstract: The influence of cooling rates in selective laser melted AlSi10Mg on fatigue properties is studied. The failure mechanisms during quasistatic and fatigue loading were analyzed using electron microscopy, X-ray computed tomography and ultrasonic fatigue testing systems. It was found that even when densification mechanism was not significantly enhanced, the morphology of defects was adopting more regularly spherical shape which is less critical under structural loading. The controlled cooling introduced microstructural homogeneity and further property enhancement of the microstructure which contributed to higher quasistatic and fatigue strength in this study and compared to the literature on the same alloy. Elimination of semi-coherent Si agglomerates on the melt pool boundaries impeded crack propagation and forced it to adjust to a perpendicular orientation to the columnar dendrites formed instead. The strengthening mechanism was shown effective in quasistatic, servohydraulic and ultrasonic fatigue tests in very high-cycle fatigue. The influence of testing at ultrasonic frequencies was analyzed through the fatigue data and influence was not significant. Analysis of the interrupted fatigue specimens in the X-ray computed tomography revealed a pore-crack interaction mechanism which was hypothesized earlier in the literature. Although impedance of crack propagation and theoretical drop of stress intensity factors at crack tips was expected, it was implied that recommence of crack propagation and the end life of the specimen will still be dependent on the local strength of the microstructure in the vicinity of the pore.